Collaborative Learning Models and Their Effect on Student Engagement and Learning Outcomes - Hanik Ristiana; Dody Riswanto; Teofilus Ardian Hopeman; Deo Renaldi Saputra; Fu'ad Sholikhi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examined the effects of structured collaborative learning on student engagement and learning outcomes in secondary education using an empirical quasi-experimental design with a non-equivalent control group. Participants were purposively recruited from one school and allocated at the class level to either an experimental group receiving cooperative learning with defined roles, peer-regulation prompts, and task interdependence, or a comparison group receiving teacher-directed instruction. Data were collected through standardized pre-test and post-test achievement measures, structured classroom observations, and a multidimensional engagement questionnaire assessing behavioral, emotional, and cognitive engagement. ANCOVA results indicated that the experimental group achieved significantly higher adjusted post-test scores after controlling for baseline differences. Engagement analyses showed greater gains across all engagement dimensions in the experimental condition, with the strongest improvement in cognitive engagement. Regression-based modeling revealed that cognitive engagement was the most powerful predictor of post-test achievement, followed by behavioral engagement, while emotional engagement showed a weaker direct association under statistical control. The findings demonstrate that structured collaboration enhances learning by strengthening metacognitive regulation and sustained cognitive investment.